Discriminating intra-parasequence stratigraphic units from two-dimensional quantitative parameters - Isla, Manuel Fermín (2021)
The intra-parasequence scale is still relatively unexplored territory in high-resolution sequence stratigraphy. The analysis of internal genetic units of parasequences has commonly been simplified to the definition of bedsets. Such simplification is insufficient to cover the complexity involved in the building of individual parasequences. Different types of intra-parasequence units have been previously identified and characterized in successive wave-dominated shoreface–shelf parasequences in the Lower Cretaceous Pilmatué Member of the Agrio Formation in central Neuquén Basin. Sedimentary and stratigraphic attributes such as the number of intra-parasequence units, their thickness, the proportions of facies associations in the regressive interval, the lateral extent of bounding surfaces, the degree of deepening recorded across these boundaries, and the type and lateral extent of associated transgressive deposits are quantitatively analyzed in this paper. Based on the analysis of these quantified attributes, three different scales of genetic units in parasequences are identified. 1) Bedset complexes are 10–40 m thick, basin to upper-shoreface successions, bounded by 5 to 16 km-long surfaces with a degree of deepening of one to three facies belts. These stratigraphic units represent the highest hierarchy of intra-parasequence stratigraphic units, and the vertical stacking of two or three of them typically forms an individual parasequence. 2) Bedsets are 2–20 m thick, offshore to upper-shoreface successions, bounded by up to 10 km long surfaces with a degree of deepening of zero to one facies belt. Two or three bedsets stack vertically build a bedset complex. 3) Sub-bedsets are 0.5–5 m thick, offshore transition to upper-shoreface successions, bounded by 0.5 to 2 km long surfaces with a degree of deepening of zero to one facies belt. Two or three sub-bedsets commonly stack to form bedsets. The proposed methodology indicates that the combination of thickness with the proportion of facies associations in the regressive interval of stratigraphic units can be used to discriminate between bedsets and sub-bedsets, whereas for higher ranks (bedsets and bedset complexes) the degree of deepening, lateral extent of bounding surfaces, and the characteristics of associated shell-bed deposits become more effective. Finally, the results for the Pilmatué Member are compared with other ancient and Holocene examples to improve understanding of the high-frequency evolution of wave-dominated shoreface–shelf systems.